Paying attention to personnel in organizational changes: the impact of hospital mergers. (13th November 2019) - Sisti, L G; Mariani, M; De Vito, C; Isonne, C; Nardi, A; Mete, R; Villari, P; Ricciardi, W; Damiani, G
Abstract: Background: The importance of paying attention to personnel satisfaction for the well-being of an organization is clearly stated also in healthcare organization. The trend of mergers of healthcare organizations represents an evident case of organizational change that could undermine personnel satisfaction if not adequately managed. The aim of our study was to investigate the impact of hospital merger on personnel perceptions and satisfaction. Methods: A systematic review of the literature was carried out by querying scientific databases and grey literature. A search string was built using keywords including: merger, healthcare, personnel, satisfaction and synonyms. Inclusion criteria were primary studies reporting the outcome of interest and set in hospitals that has undergone a merger. Studies characteristics such country setting, design and time frame of the study, number and role of personnel interviewed and main findings were extracted and narratively synthesized. Results: Search resulted in 3662 studies of which 9 were finally included in the analysis. Studies were mainly represented by post-merger qualitative research (77.8%) of which 55.6% semi and 54.4% structured interviews. Sample size ranged from 14 to 3119 and was represented by unspecified employees (55.6%), nurses and hospital executives (22.2% both). Findings showed that hospital executives consider merger positively especially regarding increased negotiation skills and costs reduction. Conversely, the other personnel mainly expressed critical issues as differences in organization of hospitals merged, goals and confirmation uncertainty, communication impairment and especially no involvement in follow-up in the post-merger phase. Conclusions: The merger process strongly impacts healthcare personnel satisfaction, depending on the role played in the organization. If an initial enthusiasm and staff engagement in pre-merger phase is seen, this is not generally followed by their proper involvement over time. Key messages: As personnel satisfaction and perceptions are strongly related to healthcare quality, they represent a central point in the merger process of healthcare organization. More attention must be paid to follow-up staff satisfaction after the merger in a continuous staff engagement to ensure the success of merger process as well as that of all organizational changes.